Altitude and latitude variations in trait-impulsivity, depression, anxiety, suicidal risk, and negative alcohol-related consequences in Argentinean adolescents - Lorena Cecilia López Steinmetz; Juan Carlos Godoy; Shao Bing Fong (Heliyon, 2020)
The aims of this research were threefold: 1) to analyze mental health state both general (GMHS, i.e., self-perceived health and psychological distress) and specific (SMHS; i.e., depression, trait-anxiety, negative alcohol-related consequences, and suicidal risk), and impulsivity-related traits (i.e., negative urgency, positive urgency, [lack of] perseverance, [lack of] premeditation, and sensation seeking) in a sample of Argentinean adolescent college students, in function of sex (women, men) and three different altitude-latitude regions (high-north, middle-center, low-south), for identifying common and specific features; 2) to analyze relationships between impulsivity-related traits and indicators of GMHS and SMHS, in the entire sample and in each altitude-latitude region, for understanding the importance of impulsivity-related traits in these forms of mental disorders; and 3) to analyze bivariate relationships between depression, trait-anxiety, negative alcohol-related consequences, and suicidal risk, in the entire sample and considering the three altitude-latitude regions, for testing two-disorder comorbidities. Scores on impulsivity-related traits differed by sex and by altitude-latitude region. GMHS and SMHS differed by sex but not by altitude-latitude region. Several relationships were found between impulsivity-related traits, GMHS, and SMHS as well as between indicators of SMHS. Some of these relationships were dependent on altitude-latitude regions, and implications of these findings were discussed.